(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Diabetes is increasingly growing in India as a possible epidemic with > 62 million diagnosed people. In relation to the possible burden of diabetes on India, India is currently facing an uncertain future. A projected US €2.2 billion is required for all Type 2 diabetes mellitus (T2DM) cases in India to be adequately handled. The burden of this disease can be minimised with several acts. However, the resources of healthcare are minimal, so diabetes treatment measures should be given priority. The current research tests the economic efficacy of antidiabetic drugs in Mumbai, India patients with T2DM. The cost-effectiveness of antidiabetic treatment in T2DM patients has been investigated in a forward-looking cross-sectional analysis. A total of 152 patients with T2DM from F-Northward, Mumbai , India, were interviewed face-to - face with a validated questionnaire. Efficacy based on costs, efficacy, adverse drug reactions, safety of administration, frequency of administering, and bioavailability have been calculated. Cost-effectiveness for non-obese participants.